Peran Wanita Sebagai Agen Pancasila: Pelatihan Pembuatan Buket Bunga Sebagai Upaya Pemanfaatan Sampah Plastik - Dyah Ayu Rahmawati; Muhammad Fauzan Tawaqal; Dewi Safitri; Malika Aulia Faradila (Universitas Negeri Semarang, 2025)
This activity is a form of implementation of service which is summarized in the Tri Dharma of Higher Education. Devotion is related to the approach of empowering women as agents of change in Indonesia based on the principles of Pancasila. The activities carried out are in the form of assistance and training which is motivated by the problem of piling up waste which needs to be managed into something useful. The increase in plastic waste and the dangers it poses to the environment will become a big problem if there is no solution. If managed properly, waste that can initially harm society can turn into something good and even become a source of additional income. The method used in this service is the method of mentoring and training for the Karangampel Village community with the main target being PKK cadre mothers. The aim of the assistance and training is as an effort to empower women in utilizing waste in the context of women's role as agents of Pancasila and as an effort to preserve the environment. This research is a form of service that we carry out to the people of Karangampel Village, Kaliwungu District, Kudus Regency to minimize the accumulation of waste. The results of this research show that women as Pancasila agents play an important role in teaching Pancasila values both within the family and society.